Electron spin density matching for cross-effect dynamic nuclear polarization. Issue 53 (5th June 2019) - Li, Yuanxin; Equbal, Asif; Tagami, Kan; Han, Songi
Abstract : A new design principle for a mixed broad (TEMPO) and narrow (Trityl) line radical to boost the dynamic nuclear polarization efficiency is electron spin density matching, suggesting a polarizing agent of one Trityl tethered to at least two TEMPO moieties. Abstract : A new design principle for a mixed broad (TEMPO) and narrow (Trityl) line radical to boost the dynamic nuclear polarization efficiency is electron spin density matching, suggesting a polarizing agent of one Trityl tethered to at least two TEMPO moieties.